Evaluation of a Rapid Syphilis Test in an Emergency Department Setting in Detroit, Michigan. Issue 7 (July 2019) - Fakile, Yetunde F.; Markowitz, Norman; Zhu, Weiming; Mumby, Kimberly; Dankerlui, Doreen; McCormick, Josh K.; Ham, David C.; Hopkins, Andre; Manteuffel, Jake; Sun, Yongcheng; Huang, Ya-lin A.; Peters, Philip J.; et al.
Abstract : Background: Syphilis transmission can be prevented by prompt diagnosis and treatment of primary and secondary infection. We evaluated the performance of a point-of-care rapid syphilis treponemal (RST) test in an emergency department (ED) setting. Methods: Between June 2015 and April 2016, men aged 18 to 34 years seeking services in a Detroit ED, and with no history of syphilis, were screened for syphilis with the RST test, rapid plasma reagin (RPR) test, and Treponema pallidum particle agglutination assay (TP-PA). A positive reference standard was both a reactive RPR and a reactive TP-PA. We compared test results in self-reported men who have sex with men (MSM) to non-MSM. Results: Among 965 participants, 10.9% of RST tests were reactive in MSM and only 1.5% in non-MSM ( P < 0.001). Sensitivity of the RST test was 76.9% and specificity was 99.0% (positive predictive value, 50.0%) compared with the positive reference standard. Three discordant specimens found negative with the RST test but positive with the reference standard had an RPR titer of 1:1, compared with 10 specimens with concordant positive results that had a median RPR titer of 1:16. The RST sensitivity was 50.0% (positive predictive value, 68.4%) compared to the TP-PA test alone. Among men seeking care in an ED, the RST detected 76.9% of participants with a reactive RPR and TP-PA. Conclusions: The RST test detected all of the participants with an RPR titer ≥1:2 but less than 20% of participants with a positive TP-PA and negative RPR. The RST test was useful to detect a high proportion of participants with an active syphilis in an urban ED. Abstract : In our study of young men seeking emergency department care, the rapid syphilis test detected 76.9% of participants with active syphilis.